2016
DOI: 10.2991/icmmct-16.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

Element size effect on the analysis of heavy-duty machine cross-rail

Abstract: Heavy-duty gantry machine plays an important role in the energy, shipbuilding, aerospace, transportation and military industry and other pillar industries, and is a manifestation of national equipment manufacturing capacity. Cross-rail is one of the key structural components, and its natural frequency affects the dynamic performance of the machine. It is difficult to obtain the accurate analysis of natural frequency by using the analytical method because of the complex internal structure. The finite element me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, it is logical to allocate finer mesh in the regions of interest (Bitencourt et al, 2015). Wang et al (2016) examined the effect of mesh size on finite element analysis of heavy-duty cross rail using ANSYS and compared simulation and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is logical to allocate finer mesh in the regions of interest (Bitencourt et al, 2015). Wang et al (2016) examined the effect of mesh size on finite element analysis of heavy-duty cross rail using ANSYS and compared simulation and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Recently several researchers have investigated the effects of mesh sizes on the accuracy of FE analysis results in various types of simulation [3][4][5][6][7][8]. Other studies have shown the relation of the mesh sizes with the accuracy of the FE modal analysis [9][10][11][12]. Nevertheless, to the best of authors' knowledge, no work focusing on the effects of mesh sizes on the FE modal analysis for the assembled structure with bolted joints has been found so far.…”
Section: Introductionmentioning
confidence: 99%